Analisis Ekonomi Politik Hilirisasi Sebagai Strategi Kemajuan dan Kedaulatan Negara Dalam Pemerintahan Prabowo–Gibran - Ndraha, Felisius Andika Fatolosa; Hidayat, Lalu Garin; Barozi, Barozi; Wahyunipan, Valentina Febbyola; Sakerebau, Irawati; Rakha, Muhammad; Subairi, Subairi (Badan Koordinasi Kegiatan Kesejahteraan Sosial, 2026)
Downstreaming of natural resources has become a strategic issue in Indonesia's economic development because for years the economy has relied on raw material exports, which are vulnerable to global price fluctuations and have low added value. This study aims to analyze downstreaming as an instrument of economic sovereignty and examine the continuity of this policy from the Joko Widodo era to the Prabowo-Gibran administration. The method used in this study is a qualitative literature study, utilizing various literature sources. The results show that downstreaming marks a significant shift from colonial and post-colonial patterns that position Indonesia in the global political economy. Within the political economy framework, downstreaming serves as a state instrument to overcome the resource curse, strengthen policy autonomy, and build long-term competitiveness through industrial integration, technological advancement, and broad job creation.